2006
DOI: 10.1038/sj.jhh.1002002
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure as a predictor of cardiovascular events in the elderly: the William Hale Research Program

Abstract: This study evaluates the association between blood pressure (BP) and the risk of developing cardiovascular disease (CVD) events in the elderly. The Morton Plant Mease Foundation has followed 4008 elderly patients 464 years of age for at least 5 years. Systolic and diastolic blood pressure (SBP and DBP) was divided into categories. Cardiovascular disease events were classified as myocardial infarction, stroke, and CVDrelated deaths reported from the National Death Index. Cox proportional hazard ratios were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Age, SBP, DBP, and past/current smoking status were linked to periodontitis in previous studies [16,17] and significantly differed between the no/ mild and moderate/severe periodontitis groups in the present study (Table 1). In addition, serum fetuin-A levels were significantly lower for moderate/severe periodontitis than for no/mild periodontitis (Table 1), which was also the case in a previous study [10].…”
Section: Discussionsupporting
confidence: 60%
“…Age, SBP, DBP, and past/current smoking status were linked to periodontitis in previous studies [16,17] and significantly differed between the no/ mild and moderate/severe periodontitis groups in the present study (Table 1). In addition, serum fetuin-A levels were significantly lower for moderate/severe periodontitis than for no/mild periodontitis (Table 1), which was also the case in a previous study [10].…”
Section: Discussionsupporting
confidence: 60%
“…Both OH and hypertension are signs of impaired blood pressure regulation [3], [4], which is associated with increased risk of cardiovascular events [5][7], falls [8][14], and mortality [15][18]. Another important risk factor of falls is impaired standing balance [13], [19], [20] resulting from the deterioration of underlying systems, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This redefinition was based mainly on the results of a number of epidemiological and clinical studies that both systolic and diastolic BPs has a strong, continuous, graded, and epidemiologically significant positive association with CVD outcomes (15). Studies have shown that compared with normal BP, prehypertension is associated with a 27% increase in all-cause mortality and 66% increase in CVD mortality (16), and is associated with CVD risk such as obesity, abnormal blood lipid profiles, subclinical atherosclerosis, elevated CRP, tumor necrosis factor-α, homocysteine, oxidized LDL, and other inflammatory markers (17).…”
Section: Discussionmentioning
confidence: 99%